REDUCTION OF EXPENSES FOR ALLOYING AND DEOXIDATION OF STEEL BY FERROALLOYS BY MEANS OF OPTIMIZATION OF TECHNOLOGIES BY DUAL SIMPLEX-METHOD USING PROGRAM MEANS IN CONDITIONS OF RUP “BMZ” - V. V. Pikul; A. E. Eroshenko (Литьë и металлургия)
The experience of implementation into the electrical steel production technological process of optimization models and logical principles of costs control is shown.